PRINSIP PENEGAKAN HUKUM PELANGGARAN PERJANJIAN LISENSI MEREK TERKENAL - Agung Sujatmiko (Masalah-Masalah Hukum, 2011)
Trade mark is a part of Intellectual Property Rights. It has been regulated by the law since 1961. The trade mark Jaw currently is Act No. 1512001. Trade mark can be well known if advertised in many medias, besides registered in many countries. Well known mark has a high economy value. It is not only profitable but also reputable, because the quality of well known mark is recoqnized by consumers. The licensing agreement is one of the ways to reduce the infringement of wellknown mark. Hence, the license agreement has an important role. It does not only give benefit for the licensor, but also for the licensee. Meanwhile, the infringement of wellknown marks that is done by third party, the licensor or the licensee can sue to the commercial court. The law enforcement of the wellknownmark's license agreement are injunction, canceliation sue and infringement sue.